Espacios y mise en abyme en Lucía Miranda (1860) de Eduarda Mansilla: hacia una deconstrucción del mito de la cautiva blanca - Kruse, Elisabeth (El Colegio de México, 2024)
In her version of the story, Eduarda Mansilla rewrites the myth of Lucía Miranda by situating the convoluted plot in Europe, a world that is completely absent from the story narrated by Ruy Díaz de Guzmán. An analysis of this new space suggests that Europe plays a role of paramount narrative importance as the setting for multiple mises en abyme. When told from this new perspective, the action originally set in America acquires a new meaning. In Mansilla’s version, the myth of the white captive steers well away from the classic dichotomy of “civilization and barbarism”, promoting the bonds with otherness and revaluating the image of the indigenous person.